Adaptation of Saccharomyces cerevisiae to toxic manganese concentration triggers changes in inorganic polyphosphates. Issue 5 (3rd June 2013) - Andreeva, Nadezhda; Ryazanova, Lubov; Dmitriev, Vladimir; Kulakovskaya, Tatiana; Kulaev, Igor
Abstract The ability of Saccharomyces cerevisiae to adapt to toxic Mn2+ concentration (4 mM) after an unusually long lag phase has been demonstrated for the first time. The mutants lacking exopolyphosphatase PPX1 did not change the adaptation time, whereas the mutants lacking exopolyphosphatase PPN1 reduced the lag period compared with the wild‐type strains. The cell populations of WT and ΔPPN1 in the stationary phase at cultivation with Mn2+ contained a substantial number of enlarged cells with a giant vacuole. The adaptation correlated with the triggering of polyphosphate metabolism: the drastic increase in the rate and chain length of acid‐soluble polyphosphate. The share of this fraction, which is believed to be localized in the cytoplasm, increased to 76%. Its average chain length increased to 200 phosphate residues compared with 15 at the cultivation in the absence of manganese. DAPI‐stained inclusions in the cytoplasm were accumulated in the lag phase during the cultivation with Mn2+.